Silencing of protein kinase D2 induces glioma cell senescence via p53-dependent and -independent pathways. Issue 7 (23rd January 2014) - Bernhart, Eva; Damm, Sabine; Heffeter, Petra; Wintersperger, Andrea; Asslaber, Martin; Frank, Saša; Hammer, Astrid; Strohmaier, Heimo; DeVaney, Trevor; Mrfka, Manuel; Eder, Hans; Windpassinger, Christian; et al.
Abstract: Background: Glioblastoma multiforme (GBM) is a highly aggressive tumor of the central nervous system with a dismal prognosis for affected patients. Aberrant protein kinase C (PKC) signaling has been implicated in gliomagenesis, and a member of the PKC-activated protein kinase D (PRKD) family, PRKD2, was identified as mediator of GBM growth in vitro and in vivo. Methods: The outcome of PRKD2 silencing and pharmacological inhibition on glioma cell proliferation was established with different glioma cell lines. Western blotting, senescence assays, co-immunoprecipitation, fluorescence activated cell sorting, quantitative PCR, and immunofluorescence microscopy were utilized to analyze downstream signaling. Results: RNA-interference (21-mer siRNA) and pharmacological inhibition (CRT0066101) of PRKD2 profoundly inhibited proliferation of p53 wt (U87MG, A172, and primary GBM2), and p53 mut (GM133, T98G, U251, and primary Gli25) glioma cells. In a xenograft experiment, PRKD2 silencing significantly delayed tumor growth of U87MG cells. PRKD2 silencing in p53 wt and p53 mut cells was associated with typical hallmarks of senescence and cell cycle arrest in G1. Attenuated AKT/PKB phosphorylation in response to PRKD2 silencing was a common observation made in p53 wt and p53 mut GBM cells. PRKD2 knockdown in p53 wt cells induced upregulation of p53, p21, and p27 expression, decreased phosphorylation of CDK2 and/or CDK4, hypophosphorylation of retinoblastoma protein (pRb), and reduced transcription of E2F1. In p53 mut GM133 and primary Gli25 cells, PRKD2 silencing increased p27 and p15 and reduced E2F1 transcription but did not affect pRb phosphorylation. Conclusions: PRKD2 silencing induces glioma cell senescence via p53-dependent and -independent pathways.